Comparing Students to Workers : The Effects of Social Framing on Behavior in Distribution Games - Jeffrey P. Carpenter; Stephen V. Burks; Eric A. Verhoogen (Institute for the Study of Labor (IZA), 2004)
To investigate the external validity of Ultimatum and Dictator game behavior we conduct experiments in field settings with naturally occurring variation in "social framing." Our participants are students at Middlebury College, non-traditional students at Kansas City Kansas Community College (KCKCC), and employees at a Kansas City distribution center. Ultimatum game offers are ordered: KCKCC > employee > Middlebury. In the Dictator game employees are more generous than students in either location. This indicates that workers behaved distinctly from both student groups because their allocations do not decrease between games, an effect we attribute to the social framing of the workplace.
Keywords: Z13; J24; C93; 330; Ultimatum game; Dictator game; fairness; reciprocity; field experiment; Verhandlungstheorie; Spieltheorie; Kognition; Arbeitsplatz; Soziale Beziehungen; Experiment; Vereinigte Staaten; Framing